The association between mental status, personality traits, and discrepancy in social isolation and perceived loneliness among community dwellers - Kumi Watanabe Miura; Takuya Sekiguchi; Mihoko Otake-Matsuura (BMC, 2024)
Abstract Background Social isolation and loneliness can co-occur; however, they are distinct concepts. There is discrepancy as some people feel lonely in social isolation, while others do not. This study sought to enhance our understanding of this discrepancy between social isolation and loneliness by investigating its related factors, with a specific focus on mental status and personality traits. Methods This study adopted a cross-sectional study design and utilized data from the 2016 and 2018 waves of the University of Michigan Health and Retirement Study. The participants were community dwellers aged 50 years and older. The outcome measurement was defined as the discrepancy between social isolation, based on six criteria, and loneliness, assessed using the three-item version of the Revised UCLA Loneliness Scale. Multinomial logistic regression models were conducted to examine the factors associated with the discrepancy. Results Participants with fewer depressive symptoms and higher extraversion were associated with the only social isolation group and the only loneliness group rather than the group consisting of those who felt lonely with social isolation. In addition, lower neuroticism was associated with the only social isolation group. Participants with fewer depressive symptoms, lower neuroticism, and higher extraversion were more likely not to feel lonely even with social isolation, compared to feeling lonely even in the absence of isolation. Conclusions Mental status and personality traits may be closely related to the discrepancy between social isolation and loneliness. This study suggests that incorporating social, mental, and psychological factors may be essential for interventions in social isolation and loneliness.